TiO_2/g-C_3N_4 water absorption coupled photocatalytic degradation of isopropanol exhaust gas - JIN Lili; WANG Wenjie; ZHOU Ying; YU Jianming; CHEN Jianmeng; LU Hanfeng* (能源环境保护)
Isopropanol, as a typical volatile organic compound released into the atmosphere, can cause harm to the environment and human health, and the coupling of aqueous phase absorption and photocatalysis is a useful technical approach for the treatment and degradation of isopropanol waste gas. In this study, TiO_2/g-C_3N_4 was used as a catalyst material to investigate its photocatalytic degradation performance of isopropanol in a gas-liquid-solid three-phase system. It was found that the photocatalytic degradation rate of isopropanol induced by visible light was significantly increased after the combination of TiO_2 and g-C_3N_4. The optimal degradation performance of 29.3% was achieved when 40%-TiO_2/g-C_3N_4 under visible light irradiation for 70 minutes, which was 4.24 times and 1.9 times higher than the photocatalytic performance of single TiO_2 and g-C_3N_4, respectively. In the continuous purification of isopropanol waste gas by the water absorption coupled photocatalyst degradation, the purification rate of isopropanol waste gas reached 61.7% after 180 minutes of visible light irradiation using 40%-TiO_2/g-C_3N_4, which was 10.6% higher than that of pure water. After five cycles of experiments, the purification rate remained above 60%, indicating good chemical stability.